Starch-vegetable fibre composites to protect food products - Fama, Lucia Mercedes (2009)
The influence of wheat bran content in biodegradable composites based on cassava starch and containing glycerol and potassium sorbate were studied. Films were produced by casting and three different fractions of wheat bran fibre were used: 1.5 mg, 13.5 mg and 27.1 mg/g of matrix. It was observed that the addition of wheat bran, which contains 40 g of water insoluble fibre per 100 g of bran, shifted the glycerol-rich phase glass transition temperature toward higher temperatures, broadening and diminishing in intensity the peak associated with this relaxation. This effect suggests that the presence of fibre led to an enhancement in the glycerol dispersion. At room temperature, an increase in fibre content did not affect density of the matrix but caused the increase of the storage modulus and the decrease of loss tangent, moisture content and water vapor permeability. Besides, the addition of fibres led to the increase of the yellow index. The improvement in water vapor barrier properties jointly with the enhancement of mechanical properties when fibre was present, lead to the idea that the composite developed can be used to protect food and extend its shelf life. © 2008 Elsevier Ltd. All rights reserved.